(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
Today, the digitalization of the education system and the implementation of innovative pedagogical technologies have become highly significant. This article analyzes current issues related to the use of blended learning technologies in tourism education. It highlights opportunities for improving students’ knowledge, developing independent thinking, and enhancing practical skills through the integration of traditional and digital teaching methods in the educational process.The study demonstrates the didactic potential of platforms such as Moodle, Google Classroom, and Zoom, as well as the effectiveness of interactive methods in teaching tourism-related subjects. Furthermore, the article substantiates the importance of blended learning in improving the quality of tourism education, developing students’ professional competencies, and preparing specialists who meet the demands of the modern labor market. The research also serves as a basis for developing scientific and practical recommendations for implementing innovative pedagogical technologies in tourism education.